Hubungan dan Manfaat Pendidikan Jasmani untuk Anak dan Remaja - Yuni Yovanka Situmorang; Muhammad Bagus Septio; Ricky; Hutasoit; Purnomo Yoel Miduk; Robert Liardon Tarigan; Bhaktiven Aryan Rumahorbo; Dony Anggreawan Wardana; Alfredo Putratama Simanjuntak; Nurkadri (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
Physical education is an important component of general education because it promotes individual growth through physical exercise and natural human movement. Physical education is a series of planned and structured learning experiences to meet the developmental and behavioral requirements of each child and adolescent. Physical education is a process of interaction between students and their environment which is handled through organized physical exercise in order to realize a complete human being which includes physical, psychomotor, cognitive, and emotional elements. In fact, many parents are not able to maximize the potential of their children, so they only need to take care of themselves physically and provide the amount of food needed, but lack of exercise stimulation. Being realistic, accepting yourself and people as they are, adapting quickly, being able to handle problems objectively, not depending on others, empathizing, having a sense of humor, being creative, and appreciating difficulties are the characteristics of emotional maturity.